2020
DOI: 10.3389/fphys.2020.596640
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Velocity Eccentric Cycling Exercise Causes Greater Muscle Damage Than Slow Eccentric Cycling

Abstract: This study aims to investigate muscle damage occurring in the early and recovery phases after fast-velocity and slow-velocity eccentric cycling. Eleven untrained men (age, 20.0 ± 1.7 years; height, 171.3 ± 6.8 cm; weight, 61.8 ± 7.7 kg; and %body fat, 13.2 ± 2.9%) performed slow-velocity maximal isokinetic eccentric cycling (slow-velocity; 30°/s) with one leg and fast-velocity (fast-velocity; 210°/s) isokinetic eccentric cycling with the other leg. Changes in maximal voluntary isokinetic concentric contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 31 publications
2
16
1
Order By: Relevance
“…As acute response to ECCs cycling, we investigated the effects of different velocities on muscle damage in one bout of ECCs cycling (Ueda et al, 2020). Our results showed that muscle damage and delayed onset muscle soreness were significantly greater in the fast (210 °/sec) than in the slow (30 °/sec) condition (Ueda et al, 2020). Therefore, similar to the above findings in elbow flexors, we concluded that the fast ECCs exercise causes greater muscle damage than the slow.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…As acute response to ECCs cycling, we investigated the effects of different velocities on muscle damage in one bout of ECCs cycling (Ueda et al, 2020). Our results showed that muscle damage and delayed onset muscle soreness were significantly greater in the fast (210 °/sec) than in the slow (30 °/sec) condition (Ueda et al, 2020). Therefore, similar to the above findings in elbow flexors, we concluded that the fast ECCs exercise causes greater muscle damage than the slow.…”
Section: Introductionsupporting
confidence: 62%
“…(Clarkson et al, 1992;Morgan and Allen, 1999;Chen et al, 2007;Ochi et al, 2016;Tsuchiya et al, 2019). The degree of muscle damage is caused by ECCs depends on the exercise duration, length, intensity (Nosaka and Sakamoto, 2001;Nosaka and Newton, 2002), repetitions (Hesselink et al, 1996;Chen and Nosaka, 2006) and velocity (Chapman et al, 2006;Chapman et al, 2008a;Ueda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would suggest that the PETP produces comparable outcomes to a traditional isokinetic ECC strength test of the knee extensors in an experimental setup that is adapted to the actual semi-recumbent ECC cycling position. However, it is important to note that differences in ECC cycling movement velocity impacts force production and muscle damage (Ueda et al, 2020 ). In their study, participants performed 5 min of ECC cycling at fast (210°·s −1 ) and slow (30°·s −1 ) velocities, with fast-velocity ECC cycling significantly impairing muscle strength and increasing muscle soreness compared to slow-velocity ECC cycling.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exercise velocity on shear modulus has rarely been examined, despite the evidence that high-velocity eccentric exercise causes significantly larger reductions in MVC than slow-velocity exercise [ 51 ]. Ueda et al [ 52 ] compared the effects of slow and fast velocity eccentric cycling, and while the latter elicited larger decreases in MVC torque, only trends for larger increase in quadriceps shear modulus immediately post-exercise were noted. Further studies are needed to reveal the effects of eccentric exercise velocity on shear modulus of different muscles.…”
Section: Changes In Shear Modulus After Damaging Exercisementioning
confidence: 99%